Analisis Penerapan Program Keselamatan Kerja PT. Proyek Pembangunan Gedung Pusat Pengujian, Pengembangan Inovasi (P31) - Safitri, Diah (Jurnal Lentera Kesehatan Masyarakat, 2023)
PT. Adhi Karya already had various K3 programs. In the implementation, there were still shortcomings and there were still work accidents. With the existing work program, the researcher wants to analyze further regarding the implementation of the Occupational Safety and Health program at PT. Adhi Karya Building Project for the Testing and Innovation Development Center (P3I) Universitas Gadjah Mada. The research conducted last was a qualitative research that uses a descriptive qualitative design. This study uses a case study design or case study. The informants interviewed consisted of 2 key informants and 4 triangular informants. Informants were selected using purposive sampling technique.The results of the research that has been done show that PT. Adhi Karya has a fairly good planning, the planning is carried out in accordance with the standards of the Permenaker No. 5 of 2018. There are shortcomings in the implementation of K3, namely the uneven distribution of K3 training provided to workers, and the implementation of the program is not in accordance with the planned schedule. The inspection is classified as good, this is indicated by the complete monthly report and routine K3 monitoring is carried out every day. The action is considered good, the company firmly gives warnings to workers who violate the K3 program. Planning, inspection and actions related to the K3 program are considered good, there are deficiencies in the implementation of the K3 program.